PENELITIAN SUMBERDAYA AIR DI BALAI BENIH IKAN (BBI) KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - SUMATERA BARAT - Garinas, Wahyu (Jurnal Hidrosfir Indonesia, 2008)
Balai Benih Ikan (BBI) is an aquaculture located in Tanah Datar district. Thisaquaculture experiencing water resources shortage. New water resources are needed for the aquaculture. The interpretation of imaging resistivity showed that at BBI, water resources lies between 70 to 100 meter depth. Aquifer thickness varies between 5 to 25 meters and were found at observation points 40 to 125 meter. Water resources at BBI was predicted found on top of the hard rock and thick layer. Water resources interpreted that the used daily as water trap on the rock layer. This existing BBI water resources are not the potential aquifer. Therefore BBI has shortage of water resources. In the future, water resources for BBI is suggested to be taken from groundwater about (100 160) meter to the west.